Strategi Pengendalian Mutu dalam Pendidikan, Pangan, dan Manufaktur: Sebuah Literature Review Sistematis 2020–2025 - Hulwatun Nisa; Ifrohatil Kamiliyah; Faidhiyatul Muna Iza; Mu’alimin Mu’alimin (Jurnal Manajemen dan Pendidikan Agama Islam, 2025)
Quality control is a crucial aspect in various fields, such as education, the food industry, and manufacturing, as it functions to maintain the consistency of service or product quality. Inaccuracy in managing quality can cause financial losses, damage an institution's reputation, and reduce stakeholder trust. Based on this urgency, this study reviews recent literature to answer the main question of how quality control strategies can be effectively applied in diverse organizations. The review was conducted through a qualitative literature review approach by exploring scientific publications via Google Scholar and the Publish or Perish (PoP) application. Article selection was based on the relevance of keywords related to quality control and was limited to publications from 2020–2025. Out of 24 articles found, filtering was done until 5 of the most relevant articles remained for in-depth analysis. The analysis reveals three main findings. In higher education, a strong internal quality system and a sustainable quality culture are needed. The food industry emphasizes the standardization of raw materials and optimization of production processes. Meanwhile, the manufacturing sector makes extensive use of statistical techniques and tiered inspections. Overall, the effectiveness of quality control requires a combination of technical, managerial, and organizational culture aspects. Future research is recommended to explore the integration of digital technology and sustainability principles in quality control practices.